Analisis Tingkat Pengangguran Provinsi Sumatra Utara Menggunakan Sign Test dan Wilcoxon Test - Miranda Siregar; Nisa Ilannur Lubis; Nirmala Sari (Interdisciplinary Explorations in Research Journal, 2024)
This study analyzes the differences in unemployment rates in North Sumatra Province in 2019 and 2022 that can be attributed to the impact of the Covid-19 pandemic. The data used were obtained from the Central Bureau of Statistics (BPS) of North Sumatra Province and cover the unemployment rates in 33 districts/cities. This study uses non-parametric statistical methods, namely the Sign Test and Wilcoxon Test, to examine whether there is a significant difference in the unemployment rate between the two years. The analysis results show that although there is a significant correlation between the unemployment rates in 2019 and 2022, the Sign Test did not find a significant difference between the two years. Thus, this research provides an overview of the impact of the pandemic on the unemployment rate in North Sumatra Province, which can be used as a consideration in formulating future employment policies.